Hijab Fashion Influencers’ Postfeminist Rebranding of Muslim Femininity on Instagram - Mora, Laura (Tijdschrift voor Genderstudies, 2025)
Abstract Social media platforms provide Muslim women with unprecedented opportunities to create empowering self-representations, with hijab fashion influencers emerging as prominent figures celebrated for challenging Islamophobic stereotypes through religious yet stylish apparel. This article adopts an intersectional feminist lens to critically examine representations of empowerment in hijab fashion content on Instagram, drawing on a feminist critique of postfeminism. This qualitative visual media analysis, consisting of compositional, semiotic and discourse analysis methods, evaluates 161 images posted by the 23 most popular hijab fashion influencers among British Muslim women between 2015 and 2021. Findings reveal that hijab fashion influencers rebrand Muslim femininity into the empowered, entrepreneurial and beautiful opposite of Islamophobic stereotypes. While the resulting aesthetic is novel and creative, this seemingly empowering visual discourse relies heavily on postfeminist, popular feminist, entrepreneurial, hyper-feminine and Eurocentric/Orientalist notions. This indicates that Islamophobia is hyper-countered by reproducing normative ideas of femininity, sexuality, ethnicity, religion and class. Ultimately, this research reveals that postfeminist logic persists in contemporary social media culture, paradoxically shaping marginalised women’s emancipatory efforts to gain online visibility and social acceptance.
Keywords: postfeminism